Avaliação da vulnerabilidade das águas subterrâneas por geoprocessamento, no Campus da UFSM - RS - Marion, Fabiano André (2009)
The intensifying demand for water in quantity and quality, and the risk of contamination caused by potentially contaminating activities, bring to light the importance of planning these activities. Thus, environmental zonings, supported by geoprocessing, which aim the identification of areas susceptible to contamination of groundwater, become increasingly important in environmental and territorial planning, and must, by law, be present as tools of urban planning and city plans. For all that, the research had as central objective, make an assessment of groundwater contamination vulnerability in UFSM Campus, located in Santa Maria, Rio Grande do Sul State (RS). The methodology is based on environmental analysis by geoprocessing, according Xavier da Silva (2001) and Mello Filho (2003). For this, the 24 wells responsible for supplying the campus, distributed in an area of approximately 1,130 ha. With the use of digital cartography, the planimetries of the following environmental variables were made: geology, depth to water, recharge, geomorphology and slope. By interpolation of potentiometric levels of the wells, a map of potentiometric surface was generated, which indicates the likelyhood of groundwater flow. By geoprocessing, the integration was carried out in the application SAGA 2007 from the decision tree based in method DRASTIC (ALLER et. al., 1987), generating The Natural Map of Groundwater Vulnerability. After, the potential points to contamination were surveyed and their probable areas of influence were evaluated, which were interacted with the natural vulnerability. From the total area under study, 47.17% of it was identified as of moderate vulnerability, 32.12% as of low vulnerability and 20.71% as of high vulnerability. The latter, although being the smaller area, is where majority of the activities occur as it is the urbanized area of the Campus. With respect to potentially contaminating activities, most of them occur on areas of high and moderate vulnerability, and the underground flow (probable dispersion of contaminants) is towards north, to the Camobi District. These results will be use as the basis for groundwater conservation plans, integrated to the guidelines of the Campus City Plan of the UFSM, which is in its elaboration phase.